2007
DOI: 10.1002/adfm.200600959
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Nanometric Cubic and Tetragonal Zirconia Obtained by High‐Pressure Pulsed Electric Current Sintering

Abstract: Transparent samples of cubic (8 mol % yttria) and tetragonal (3 mol % yttria) zirconia were prepared from nanometric powders by the pulsed electric current sintering process. The crystallite size of the resulting dense samples was about 50 nm in both cases. The consolidation pressure had a positive effect on the occurrence of transparency for both modifications. Transmittance in the near infrared for 1 mm thick samples is above the 60 % for the cubic (8 %YSZ) and above 50 % for the tetragonal (3 % YSZ) zirconi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
187
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(200 citation statements)
references
References 33 publications
8
187
2
3
Order By: Relevance
“…[43] For sintering temperatures below 1000°C, steel and refractory metals such as TZM molybdenum alloys, copper-beryllium, alumina, [243] silica, [244] and even concrete [245] were used. Anselmi-Tamburini et al [141] used binder-free tungsten carbide parts with silicon carbide inserts. Double-walled tool concept with inner ceramic die and outer graphite mantle has also been proposed.…”
Section: Near Net Shape Processing and New Tool Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…[43] For sintering temperatures below 1000°C, steel and refractory metals such as TZM molybdenum alloys, copper-beryllium, alumina, [243] silica, [244] and even concrete [245] were used. Anselmi-Tamburini et al [141] used binder-free tungsten carbide parts with silicon carbide inserts. Double-walled tool concept with inner ceramic die and outer graphite mantle has also been proposed.…”
Section: Near Net Shape Processing and New Tool Conceptsmentioning
confidence: 99%
“…[142] Optically anisotropic ceramics are even more challenging, as the transparency decreases drastically as grain size increases, and alumina, [143][144][145][146] tetragonal zirconia, [147] or hydroxyapatite [148] have been synthesized with improving success. Compared to standard free sintering in vacuum followed by HIP, the definite advantages of FAST/SPS are: (i) one single set-up required for densification and (ii) shortening of the process cycle.…”
Section: Transparent Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The zirconia core is less translucent than other dental all-ceramic materials such as glass-infiltrated ceramics, which is known for its good esthetic properties (11,12). Translucency of zirconia is related to the amount and type of additives, the sintering temperature, the atmospheric conditions during the sintering process and the heating methods (13)(14)(15)(16).…”
Section: Razina Jezgrementioning
confidence: 99%
“…17) A recent study using the spark plasma sintering method also showed that a fine-sized pore gives less effect as compared with pores with sizes comparable to wavelength. 14) Therefore, both miniaturization of the residual pores and their elimination are favorable for promoting transparency.…”
Section: )mentioning
confidence: 99%